2015
DOI: 10.1136/bcr-2015-211582
|View full text |Cite
|
Sign up to set email alerts
|

Water-only fasting and an exclusively plant foods diet in the management of stage IIIa, low-grade follicular lymphoma

Abstract: Follicular lymphoma (FL), the second most common non-Hodgkin's lymphoma (NHL), is well characterised by a classic histological appearance and an indolent course. Current treatment protocols for FL range from close observation to immunotherapy, chemotherapy and/or radiotherapies. We report the case of a 42-year-old woman diagnosed by excisional biopsy with stage IIIa, grade 1 FL. In addition to close observation, the patient underwent a medically supervised, 21-day water-only fast after which enlarged lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, intentional weight loss could be perceived as advantageous in cancer patients given that it indicates maximal metabolic pressure being exerted upon cancer cells. In accordance with this possibility, preliminary reports of fasting and ketogenic diet strategies in patients with advanced tumours, including GBM, have shown that weight loss in the range of 13-28% can be associated with highly positive therapeutic outcomes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, intentional weight loss could be perceived as advantageous in cancer patients given that it indicates maximal metabolic pressure being exerted upon cancer cells. In accordance with this possibility, preliminary reports of fasting and ketogenic diet strategies in patients with advanced tumours, including GBM, have shown that weight loss in the range of 13-28% can be associated with highly positive therapeutic outcomes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, when correctly executed, fasting and ketogenic diet protocols can comfortably meet a patient's nutritional needs while exerting a sparing effect on lean mass (38), with some studies indicating that ketogenic diets induce weight gain in cancer patients with cachexia (39). Furthermore, several case reports involving KMT have shown that significant intentional weight loss (up to 28% of initial body weight) can be associated with positive outcomes in patients with GBM and other advanced cancers (31,32,40,41). We cannot draw firm conclusions with respect to the mechanism of KMT in our patient, or its impact on her long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although most of these studies involved prolonged fasts, the fasts were still relatively short (the study with the longest fasts averaged roughly 90 hours per fast) [ 110 ]. Longer fasts in cancer patients are rare, although there have been two case reports of patients with advanced cancer undergoing fasts of 7-21 days in duration, both of whom showed long-term (and ongoing) tumour regression and survival in the absence of any standard cancer treatments [ 112 , 113 ].…”
Section: Metabolic Strategies: Restoring Mitochondria Functionmentioning
confidence: 99%